Wierność epistolarna Witkacego - Szkudlarek, Ewa (Przestrzenie Teorii, 2011)
Epistolary writing has been known for ages and has won a significant position in the history of literature. One of the most intriguing exchanges of letters known from the 20th century started nine days before the wedding of the renowned artist Stanisław Ignacy Witkiewicz with an aristocrat Jadwiga von Urunh. The first letter is dated to the 21st of March 1923 and the last on the 24th of August 1939. The letters of Witkacy to his wife have been for many years surrounded by a veil of mystery. They can be read as a history of a certain relationship, a study of loneliness, a historical and social life chronicle or as a comment on artistic activity. The set comprises 1278 letters, postcards and wires. In this edition it is divided into two equal parts of which the first one includes the letters, while the second presents the commenting notes written by Professor Janusz Degler. The editors divided the whole set into four parts of which three volumes of Witkacy’s letters to his wife from the years 1923–1927, 1928–1931, 1932–1935 have already been published. Unfortunately, none of the letters written by Jadwiga to her husband has been found, so we know the correspondence exclusively from the side of a daily writer Stanisław Ignacy Witkiewicz.